(X-3) × (y+3) = 12 va rog,rapid!
Răspunsuri la întrebare
Răspuns de
0
6 x 2 = 12 ; 4 x 3 = 12
X - 3 = 4 ; X = 4 + 3 ; X = 7.
y + 2 = 3 ; y = 3 - 2 ; y = 1.
( X - 3 ) x ( y + 2) = 12 => ( 7- 3 ) x ( 1 + 2 ) = 4 x 3 = 12.
X - 3 = 4 ; X = 4 + 3 ; X = 7.
y + 2 = 3 ; y = 3 - 2 ; y = 1.
( X - 3 ) x ( y + 2) = 12 => ( 7- 3 ) x ( 1 + 2 ) = 4 x 3 = 12.
Maracris07:
MULTUMESC!
Alte întrebări interesante
Matematică,
8 ani în urmă
Franceza,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă